THE CONTROVERSY OF NON-MUSLIM LEADERSHIP: A Critical Analysis of Bahtsul Masā’il Nahdhatul Ulama’s 1999 Decision - Kurnia, Muhammad; Hidayat, Rahmat; Hayatullah, Imam Khomaeni (TAJDID: Jurnal Ilmu Ushuluddin, 2025)
This study examines the controversy over non-Muslim leadership in Indonesia, a Muslim-majority country, through the perspective of decisions made by the Lajnah Bahtsul Masā’il (LBM) of Nahdlatul Ulama (NU). Using qualitative analysis of NU congress records from 1926 to 2000 and classical fiqh literature, the study identifies two dominant views. First, there is an absolute prohibition based on Al-Ma’idah (5:51), which emphasizes the prohibition of appointing non-Muslims as leaders. This verse is used as a reference to assert a strict theological position regarding leadership. On the other hand, there is an alternative view permitting non-Muslim leadership in emergency situations, provided that the leader comes from Ahlul Dzimmah and is under strict supervision. This perspective demonstrates flexibility in the interpretation of Islamic law, especially in the context of urgent social and political needs. In certain cases where a non-Muslim leader is considered more capable of managing public affairs, NU shows a pragmatic stance aligned with the Shafi’i fiqh principles that prioritize the welfare (maslahah) of the community. These findings reveal a tension between textual interpretation and contextual necessity, highlighting NU’s pragmatic approach to addressing pluralism challenges in Indonesia. Thus, this study contributes to debates on Islamic law and pluralism and encourages dialogue to bridge religious norms with democratic governance. In conclusion, it is important to develop a more inclusive and adaptive understanding of leadership in diverse societies to create harmony between religious values and modern societal needs.